Interspecies Anticancer and Antimicrobial Activities of Genus Solanum and Estimation of Rutin by Validated UPLC-PDA Method. (3rd July 2018) - Alajmi, Mohamed Fahad; Alam, Perwez; Rehman, Md. Tabish; Husain, Fohad Mabood; Khan, Azmat Ali; Siddiqui, Nasir Ali; Hussain, Afzal; Kalam, Mohd. Abul; Parvez, Mohammad Khalid
Abstract : Solanaceae is one of the highly diverse plant families of which Solanum is the largest genera (1700 species) containing several pharmacological properties like anticancer and antimicrobial. This motivated us to explore the anticancer (against HepG2, HEK-293, and MCF-7 cells) and antimicrobial (against S. aureus, E. coli, P. aeruginosa, and C. albicans ) properties of S. schimperianum, S. villosum, S. coagulans, S. glabratum, S. incanum, and S. nigrum along with rutin estimation by UPLC-PDA method. Of the studied Solanum extracts, S. nigrum exhibited significant cytotoxic property against HepG2 (IC50 : 20.4 μ g/mL) and MCF-7 (IC50 : 30.1 μ g/mL); S. coagulans showed toxicity against HepG2 (IC50 : 28.4 μ g/mL) and HEK-293 cells (IC50 : 25.7 μ g/mL) compared to 5-Fluorouracil (standard). Compared to these, extracts of S. coagulans and S. glabratum exhibited relatively high antimicrobial potency (MIC: 0.4-1.6 mg/mL). Nonetheless, all Solanum extracts significantly reduced the biofilm against PAO1-strain. Rutin was detected in all extracts with the highest content (53.79 μ g/mg) in S. coagulans that supported its strong antimicrobial and anticancer properties. Molecular docking analysis showing strong binding of rutin with human DNA and proteins (DNA Topoisomerase II α and E. coli DNA gyrase B) supported the anticancer and antimicrobial activities of Solanum species.